EXTINGUISHING FIRE, IGNITING TOLERANCE: FIRE FIGHTER COMMUNITY, CIVIL CULTURE AND TOLERANCE - Rosadi, Sandi (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
The correlation between civil society and democracy is a big discussion in academic world. Democracy that engenders a civic culture usually linked into a tolerant behavior in society. This study aims to understand how the participation of individuals in civil society, in this case is BPK (fire fighter community) in Banjarmasin, cause them to become more tolerance in a pluralistic society. In addition, this study also examines whether the involvement of member to BPK in Banjarmasin make them as an individual who is more attentive and tolerant towards different groups or vice versa. This study argues that there is a correlation between a personal membership in civil society with their augmentation in tolerance attitude. The case of fire fighter community in Banjarmasin shows an establishment of a brotherhood among its members. The attitude of ?sanak ikam? or your brother brings up the attitude of civic members' tolerance of all the differences that exist in other individuals in general and differences in members of BPK in particular. Furthermore, on personal level, a member's attitude towards tolerance can also be affected by the diversity of members in BPK who their affiliated. However, BPK has the possibility of being a place for political contestation. On one side BPK has been playing a role in fostering tolerance in Banjarmasin society, on the other hand, it is possible in the future become a double-edged knife that even destroys the tolerance that has been formed.